2012
DOI: 10.2147/ijn.s34036
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline hydrochloride nanoliposomes inhibit the production of TNF-α in LPS-stimulated macrophages

Abstract: Background:As an adjunctive treatment of chronic periodontitis, it seems that the application of periocline or the other antimicrobials is effective against periodontopathogens. In this study, nanoliposomes were investigated as carriers of minocycline hydrochloride and the inhibition effects of minocycline hydrochloride nanoliposomes on the proliferation and lipopolysaccharide (LPS)-stimulated production of tumor necrosis factor-α (TNF-α) of macrophages were elucidated. Methods: After stimulation with 10 µg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…It is important that the nature of immune suppression in gangliosides is determined because of their potential for reducing xenotransplantation immune rejection. Moreover, the mechanism of cell-mediated xenotransplantation rejection is only partially understood (Mejia-Laguna et al 1971;Ozawa et al 1992;Lin et al 1997;Magnusson et al 2005;Jung et al 2009;Song et al 2010;Liu & Yang 2012). In particular, it is likely that the innate immunity effects that are mediated by gangliosides will influence cell functions and contribute to the strength and complexity of xenotransplantation rejection (Platt et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It is important that the nature of immune suppression in gangliosides is determined because of their potential for reducing xenotransplantation immune rejection. Moreover, the mechanism of cell-mediated xenotransplantation rejection is only partially understood (Mejia-Laguna et al 1971;Ozawa et al 1992;Lin et al 1997;Magnusson et al 2005;Jung et al 2009;Song et al 2010;Liu & Yang 2012). In particular, it is likely that the innate immunity effects that are mediated by gangliosides will influence cell functions and contribute to the strength and complexity of xenotransplantation rejection (Platt et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In another paper, Liu et al developed nanoliposomes as carriers of an anti-inflammatory action drug—minocycline hydrochloride [ 108 ]. The nanoliposomes consist of hydrogenated soy phosphatidylcholine and cholesterol (in a 2:1 molar ratio) and have been prepared via extrusion.…”
Section: Liposomesmentioning
confidence: 99%
“…21 "Minocycline" belongs to the tetracycline family, but it has a broader antibacterial spectrum than other tetracyclines and can be applied in the treatment of periodontitis. 21,22 It has been demonstrated that minocycline can affect the immune response caused by cell factors and have a beneficial effect on periodontal health. 23 In this study, minocycline was encapsulated in poly(ethylene glycol)-poly(lactic acid) (PEG-PLA) NPs, which are metabolized to nontoxic CO 2 and H 2 O in the body, 24 and the pharmacokinetics and pharmacodynamics of this formulation were investigated through a periodontitis model in beagle dogs.…”
Section: Introductionmentioning
confidence: 99%